The Percentage Of Internal Organ Weight Of Broiler Chickens Fed Containing Corn Leaf Flour With Different Levels - Nuraini, Alia Putri; Ellen J. Saleh; Muhammad Mukhtar (International journal of technology and education research, 2026)
This research aims to determine whether feeding corn leaf meal at different levels can increase the percentage of internal organ weight in broiler chickens. This study used a completely randomized design (CRD), consisting of 5 treatments and 5 replicates. The analysis used was Analysis of Variance, and if there was a significant effect, it was followed by Duncan's multiple range test. Experiments were given as follows: P0 (100% commercial feed) (Control), P1 (feed with 5% corn leaf flour), P2 (feed with 10% corn leaf flour), P3 (feed with 15% corn leaf flour), P4 (feed with 20% corn leaf flour). The results showed that the addition of corn leaf meal in the diet had no significant effect (P>0.05) on the percentage of liver, heart, and stomach in broiler chickens. The addition of corn leaf meal in the feed at levels of 5-20% had no significant effect, but it could increase the weight of internal organs in broiler chickens.